As Ariranhas (Pteronura brasiliensis Zimmermann, 1780) do Parque Nacional do Viruá: uso do espaço e caracterização de hábitats e microhábitats - Ossa Restrepo, David Maurício (2009)
This study is over ecological Giant Otter’s (Pteronura brasiliensis) aspects of the low river Branco, National Park of Viruá, Roraima. The general objective was to verify if the studied community's ecological parameters (space use and behavior) are similar to them besides communities of giant otters found in literature. The study was accomplished at a stretch of 53 km at the Iruá river from his mouth in ascending direction, It was possible to identify the spaces utilized for dens, latrines and camp sites. The giant otters utilize the following places: Border of rivers and banks of marginal dike for the construction of dens; areas exposed on banks are cleaned for that serve like latrines; and sand banks and woods are used for rest and to patrol the places (camp sites). They were observed among 1 and 4 entries by den, whose aspect is oval. With respect to the frequency of use of dens, 23 % of these were being occupied by giant otters. The associates to dens were near the 25 % of the latrines. Four groups of dens at the stretch were identified. Dens were categorized like: In use (9), obsolete (23), and destroyed (5). Giant Otter’s groups were observed in 13 occasions (sightings), varying among 1 and 12 individuals for group. The frequency of sightings went from 1 to each 8 kilometers approximately. Two giant otter’s groups were identified, the first close to the Iruá’s mouth, compound even for 5 individuals; the second more distant group of the mouth with groups fixed for over 5 individuals. Among two groups there is an area where giant otters were not found. Two types of expressions of the behavior were observed in giant otters, with respect to vocalization and to movements of the body. Aspects related to these parameters are discussed; In general, the patterns observed in giant otter’s groups of the area of study agree with literature.